Peer Mentoring: Exploring the Impact on the Learning Culture of a Business Institute in Pakistan - Shumaila Omar; Syed Irfan Hyder; Naziha Ali Baber (International Journal of Experiential Learning & Case Studies)
University education is a new transition from school to undergraduate programs for underprivileged students. Recruiting students from rural areas of Pakistan challenge teachers to teach at a Higher Education while teaching underprivileged students struggling for a better future. The aim of this paper was to introduce peer mentoring between the Business and Professional Speech (BPS) students and the freshmen. The researcher being course faculty of both the Business and Professional Speech and Foundation English students undertook the experiential learning project. The initiative for the project was to explore the impact of peer mentoring on the learning culture of a Business Institute in Pakistan, subsequently, highlighting the skills of lifelong learners in the 21st century of global citizenship. The aim of this paper was also to investigate the strength of mentors in keeping the course objectives aligning with students’ interpersonal, intrapersonal and public communication abilities, at developing students’ critical thinking and problem-solving skills. Kolb’s experiential learning model (1984) was implemented to carry out the project; whilst, students direct data of interviews, video clips, pictures, questionnaires and documents were used to validate the research. Findings demonstrate the benef icial impact on the cyclical learning between the faculty, BPS and freshmen in terms of their improved results, retention of reading tasks and exposure to the real-life challenges of the diverse groups at the university. Peer mentoring could be the possibility of bringing about a change in society if introduced at universities in Pakistan.